Mechanical Performance and Corrosion Behaviour of Aluminum7075 Reinforced by Nano-Titanium dioxide - Raouf Mahmood Raouf; Lubna Ghalib; Ahmed K. Muhammad (مجلة بغداد للعلوم)
In this study, the stir casting technique (SCT) was applied to form aluminium (Al) nanocomposites with various weight percentages of nanotitanium dioxide powder (TiO2). The structural, mechanical, and corrosion properties of nanocomposites were investigated. The microstructure was taken by scanning electron microscopy (SEM), while the crystal structure of the specimens was obtained using X-ray diffraction (XRD). In addition, nanocomposites were immersed in 0.5 M HCl solution for potentiodynamic and corrosion rate measurements. The results showed that the best specimen is 0.03%, as it increased by 23% for hardness, but the tensile strength increased to 52%. Whereas, SEM images of the specimens reinforced with nanoparticles showed a clear homogeneity and diffusion of nanoparticles in the matrix. So, the addition of TiO2 nanoparticles to aluminium metal improved the hardness and tensile strength of the nanocomposites appreciably. The corrosion results showed that nanocomposite materials have higher corrosion resistance than Al7075-based composite materials.